INDIAN MEDICINAL PLANTS USEFUL IN TREATMENT OF GOUT: A REVIEW FOR CURRENT STATUS AND FUTURE PROSPECTIVE - Kapoor, Bhupinder; Kaur, Gagandeep; Gupta, Mukta; Gupta, Reena (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of this review is to collect and document information on the Indian medicinal plants with anti-gout potential. Methods: Bibliographic investigation was carried out by consulting worldwide scientific databases, analyzing Ayurvedic text books and research journals. The search terms were gout,â€ uric acid,â€ hyperuricemia,â€ xanthine oxidase (XO) inhibitor and uricosuric.â€ Herbal keywords included herbal medicine,â€ medicinal plant,â€ natural products,â€ phytomedicineâ€ and phytotherapy.â€ Result and Conclusion: Medicinal plants have been used to treat various ailments since ancient times; hence, ethnobotanical investigations play an important role in pharmacological studies. In India, traditional medicines are being practiced for the treatment of gout and other rheumatic disorders from ancient time. This review provides a comprehensive summary of 130 Indian plants which have been mentioned in ancient literature or used traditionally for the treatment of gout. Out of these, 41 plants have been reported to possess XO inhibitory activity. Further, isolated phytoconstituents having promising XO inhibitor activity are also included in this review. Although a variety of medicinal plants with anti-gout potential have been found in the literature, there is limited information on evaluation of anti-gout activity of isolated phytoconstituents. The current review contains a detailed discussion of the potential of medicinal plants for treatment of gout. Â